The damage scale concept and the critical plane approach. Issue 8 (20th June 2017) - Anes, V.; de Freitas, M.; Reis, L.
Abstract: Critical plane criteria seek the plane in which their damage parameter has its maximum value. On this plane, the fatigue damage of both normal and shear stresses is updated to the same damage scale by a constant, typically based on material normal/shear fatigue limits. This paper focuses on the damage scale concept under a stress‐based critical plane standpoint, and the main objective is to evaluate its performance. To perform this study, data from the high strength steel 42CrMo4 were considered. Five proportional loading paths with different stress amplitude ratios and stress levels were analysed using 2 different multiaxial fatigue criteria, namely, the Findley critical plane model and the stress scale factor equivalent shear stress. Results show that the damage scale between normal and shear stress components varies accordingly to the loading plane direction considered.